Comparison Between The Efficacy of Fentanyl Continuous Infusion and Intratechal Morphine for Pain After Cesarean Section - Putro, Prabowo Wicaksono Yuwono; Nasihun, Taufiqurrachman (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2017)
Background: Intrathecal morphine has been shown to be effective for pain after cesarean section with possible side effect including delayed respiratory depression, nausea vomiting and pruritus. Fentanyl continuous infusion fixed base infusion rate with disposable elastomeric pump is an alternative to intrathecal morphine but has not been been widely studied.Objective: to compare the effectiveness between fentanyl continuous infusion fixed base infusion rate using disposable elastomeric pump and intrathecal morphine.Methods: in a Randomized Controlled Trial (RCT), 56 patients meeting the inclusion criteria were divided into two groups: Morphine group (n=28): spinal anesthesia 10 mg Bupivacaine Heavy 0.5% + 100 mcg morphine; Fentanyl group (n=28): spinal anesthesia 10 mg Bupivacaine Heavy 0.5% + fentanyl continuous infusion 0.5 mcg/kg BW/hour using disposable elastomeric pump after delivery. Data analysis: Mann-Whitney test at the level of significance p<0.05.Results: Analgesic effect of Fentanyl group was as effective as that of Morphine group. NRS score difference was significant only in measurement taken 6 hours after surgery (p=0.034). Mean NRS score for Morphine and Fentanyl were 68±1.02 and 1.11±0.832, respectively. Both group were effective in preventing increased cortisol level measured 6 hours after surgery, mean value group Morphine and Fentanyl were 15.053±8.664 and12.162±8.623, respectively.There were no statistical significant difference between groups (p=0.114). No significant difference in side effect between the groups was found.Conclusion: Fentanyl continuous infusion 0.5 mcg/kg BW/hour using disposable elastomeric pump is as effective as intrathecal morphine 100 mcg/kg BW/hour